Splish! Splash! - Herman, Gail. 1959-; Basso, Bill. (New York : Scholastic Inc., 2003)
When it rains on the first day of summer, Molly's mother lets her invite her friends to a pool party...inside!
"Kindergarten-Grade 2."--Cover.
G1
Keywords: Rain and rainfall -- Juvenile fiction; Swimming -- Juvenile fiction; Parties -- Juvenile fiction